Web writing for museums: analyzing principles and best writing practices for digital media through the “wise stones (Pedras Sabidas) accessible circuit” case study - Veiga, Ana Cecília (2019)
Museum communication professionals have developed theories and knowledge about museum texts and institutional discourse. However, over the past decades, the digital revolution has brought about deep changes in our behavior with respect to written words in digital support. Such support can be found not only on the web (virtual museums and institutional websites), but also in exhibit facilities, through interactive interfaces, apps, QR Codes and other digital media that form our contemporary exhibits. This requires a change in current writing paradigms toward the best ways to impart knowledge in museums and over the Internet. Therefore, the various players responsible for museum texts (curators, museologists, historians etc.) are now required to master several previously non-existent skills. In this work we want to discuss writing in museums starting from digital support, both for the web and for interactive exhibitors. We created writing guidelines based on new web writing techniques and current demands, without prejudice to the primary functions of a museum. As an example of our reflections, we intend to study the case of the Project “Wise Stones (Pedras Sabidas) Interactive Exhibitors’ Accessible Circuit”, which is a roadmap consisting of accessible digital interfaces, exposed at the Mines and Metal Museum (MM Gerdau) in the City of Belo Horizonte, Brazil. This Project received an award from the Ibermuseus Program in 2016. In this work we analyze, therefore, the written production both of the project’s website and of the interactive interfaces’ content, exemplifying, through the Wise Stones Accessible Circuit, that which we define as “exhiwriting” (digital exhibition writing). This is a proposal of web writing principles for museums, encompassing the best writing practices for social media and for the web, without giving up the sophistication and depth required by museum communication, thus fulfilling our museums’ social function.